Myocardial Fibrosis: Unveiling the Hidden Scars of the Heart - Hassan, Summer; Barrett, Carolyn J; Crossman, David J (Medicine and Medical Research: New Perspectives Vol. 6, 2024)
Myocardial fibrosis is regarded as a significant pathological process in the development of heart illness, as well as a potential target for future therapies. Despite this knowledge, fibrosis is not routinely assessed in clinical practice. This is primarily due to the difficulties in obtaining an accurate non-invasive assessment of fibrosis. Moreover, there is a clear discrepancy between the clinical understanding of myocardial fibrosis, where fibrosis is predominately studied with comparatively low-resolution medical imaging technologies like Echocardiography, Computed Tomography (CT), or Magnetic Resonance Imaging (MRI), and the detailed visualisation possible in basic science laboratories using molecularly specific fluorescence microscopes at the microscopic and nanoscopic scales. Current medical imaging technologies for assessing fibrosis, including echocardiography and MRI, provide valuable information but are limited by their resolution and specificity. While these modalities are essential in the clinical setting, they fall short of capturing the intricate details of fibrotic changes at the cellular and molecular levels. This gap highlights the need for greater microscopic and nanoscopic analysis of human tissue, which can be addressed through the increased utilisation of human tissue available from endomyocardial biopsies and cardiac surgeries. The relatively new field of molecular imaging offers a promising solution to this challenge. Molecular imaging techniques aim to translate research findings into clinical practice by non-invasively monitoring the molecular signature of fibrosis in patients. These advanced imaging methods have the potential to provide high-resolution insights into the fibrotic process, enabling more accurate diagnosis, better monitoring of disease progression, and the evaluation of therapeutic interventions. As the understanding of myocardial fibrosis deepens, it becomes clear that bridging the gap between clinical practice and basic research is essential. By integrating advanced imaging technologies and leveraging human tissue samples, the ability to diagnose and treat myocardial fibrosis can be enhanced more effectively. This comprehensive approach holds promise for improving patient outcomes and advancing the field of cardiology.